Digital Technologies for Agricultural and Rural Development in the Global South 2018
DOI: 10.1079/9781786393364.0111
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impacts of Mobile technology on smallholder agriculture.

Abstract: This chapter presents the case of how information and communication technologies (ICTs), particularly mobile phones, impact agricultural development by facilitating step-wise changes in smallholder farmers' information and agriculture practices in rural Ghana. The study shows how mobile phones introduced among smallholder farmers create 'hybrid' information practices that are consistent with both existing cultural-historical norms around farming and ICT use (a smallholder logic) and with policy imperatives aim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…For example, pastoralists in Ethiopia placed their mobile phones on high objects to access weak mobile networks ( Debsu et al, 2016 ). Numerous other studies observed users making DETs useful ( Karubanga et al, 2019 ; Karanasios et al, 2018 ; Maredia et al, 2018 ; Gandhi et al, 2007 ). For example, farmers in Gujarat leveraged a voice-based agronomy forum to improve social status, entertain guests, share poetry and jokes, keep awake while irrigating and develop off-farm businesses ( Patel et al, 2010 ).…”
Section: Discussionmentioning
confidence: 93%
“…For example, pastoralists in Ethiopia placed their mobile phones on high objects to access weak mobile networks ( Debsu et al, 2016 ). Numerous other studies observed users making DETs useful ( Karubanga et al, 2019 ; Karanasios et al, 2018 ; Maredia et al, 2018 ; Gandhi et al, 2007 ). For example, farmers in Gujarat leveraged a voice-based agronomy forum to improve social status, entertain guests, share poetry and jokes, keep awake while irrigating and develop off-farm businesses ( Patel et al, 2010 ).…”
Section: Discussionmentioning
confidence: 93%
“…Sources: Aker (), Armstrong et al (), Courtois and Subervie (), Fafchamps (), Karanasios and Slavova (), Lyon (), Noman et al (), Slavova and Karanasios (), World Bank ().…”
Section: Agriculture and Ict In Rural Africaunclassified